Pengembangan Media Pembelajaran E-Mind Mapping Berbasis Flipbook pada Mata Pelajaran Fisika SMA Kelas 11 - Widya Halimah; Putri Octafianus; Farid Nasihin Jamahsari; Dasmo Dasmo (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This development research aims to produce an E-Mind Mapping learning media based on flipbook physics for grade 11 high school students on equilibrium and rotational dynamics, elasticity and Hooke's law, as well as static and dynamic fluids. This research is a development research (R&D) using the R2D2 (Recursive, Reflective Design and Development model) model with the stages, namely, determining learning materials, analyzing needs, developing learning materials, compiling E-Mind Mapping concepts, editing materials into. e-learning. mind mapping and combining it into a flipbook, production, validation and testing, revision and refinement. However, in this study, it was only carried out until the validation stage. The results of the study show that the material displayed in this flipbook-based E-Mind Mapping has met the eligibility criteria in the very good category, and the flipbook-based E-Mind Mapping learning media has met the eligibility criteria in the good category. Overall, the flipbook-based E-Mind Mapping learning media has met the eligibility criteria in the good category.